(untitled) (Global Journal of Science Frontier Research, 2014)
Assuming that a particle follows the discrete Bernoulli process with a step size proportional to one over twice its mass and that the vacuum is made up of particles with the reduced Planck mass, one can derive both Newton’s Law of Gravitation and Coulomb’s Law of Electric Force using slightly different parameters of the process. Two classes of experiments, which could affirm the hypothesis, would indicate a preferred reference frame.